Sustainable Development Goals in academic publishing: impacts of SDG Publishers Compact and EASE Environmental Manifesto - Nikita Lad; Iva Grabarić Andonovski; Dana Compton; Jo Wixon; Mary Hodgson (European Science Editing)
Background: To enlist publishers and journals in promoting the UN Sustainable Development Goals (SDGs), the United Nations and the International Publishers Association (IPA) launched the SDG Publishers Compact in 2020, and the European Association of Science Editors (EASE) published its Environmental Manifesto, a set of recommendations for journal editors on how to contribute to reducing a journal’s carbon footprint. It is important to monitor the impact of these initiatives on journal policies for developing future recommendations.Objectives: The EASE and the Higher Education Sustainability Initiative (HESI) SDG Publishers Compact Fellows developed a survey to assess the progress made by signatories to the SDG Publishers Compact, detect obstacles that prevent other publishers or journals from signing the compact, assess awareness and implementation of the EASE Environmental Manifesto, and identify other initiatives that promote SDGs.Methods: A multi-stakeholder group was formed, which included editors and both commercial and non-profit publishers, to design questions suited to journals and organizations at different stages of sustainability action. The survey was designed using SurveyMonkey, introduced in an online workshop, distributed through mail-ing lists to more than 2000 addresses, and promoted on social networks, and a total of 79 responses were collected and discussed.Results: Most respondents were representatives of smaller journals based in Europe. The majority were aware of the SDGs, but only half were aware of the SDG Publishers Compact, and only 17 (22%) were signatories to the Compact. Lack of awareness was the major reason for not joining the initiative, followed by lack of time or resources. Respondents focused mostly on quality education, and the majority were acting to achieve at least one SDG. Signatories to the compact mostly have a written environmental policy, have appointed an environmental officer, and are acquiring content related to the SDGs and promoting related activities. Non-signatories are also acting to minimize their environmental impact but have not considered the SDGs in their workflows. Both groups mainly do not have a dedicated budget to achieve the SDGs and have not completed a baseline of their activities. Activities undertaken to reach the SDGs had the most effect on community awareness. Half the respondents were members of EASE and were taking actions aligned with the Environmental Manifesto, mostly towards reducing their journal’s carbon footprint, and 25% are fol-lowing other initiatives aimed at achieving the SDGs as well.Conclusions: The survey showed that editors of small academic journals were not aware of the SDG Publishers Compact, although most of them are acting to achieve at least one SDG. Signatories to the Compact are implementing SDGs into their work-flows and practices, which shows the importance of the initiative. Greater efforts should be undertaken to make the editors of smaller journals aware of the Compact, encourage them to become its signatories, and provide them with more resources and metrics for monitoring their activities.